2010
DOI: 10.1200/jco.2010.28.6856
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Allogeneic Hematopoietic Stem-Cell Transplantation From Matched Related and Matched Unrelated Donors in Younger Adults With High-Risk Acute Myeloid Leukemia: German-Austrian Trial AMLHD98A

Abstract: Allogeneic HSCT in younger adults with high-risk AML has a significant beneficial impact on outcome, and allogeneic HSCT from MRD and MUD yields similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 30 publications
10
169
3
2
Order By: Relevance
“…Patients with good risk cytogenetics such as abn [16] or t(8; 21) can be spared from the toxicity of SCT, while patients with high risk cytogenetics appear to benefit from SCT, with an estimated 44% probability of surviving 5 years after CR1, compared with 15% or less after chemotherapy [2]. Several reports have confirmed this significant advantage of SCT in high risk AML, and it is currently highly recommended not to delay SCT in this population [3][4][5]. Among patients with high risk AML, the coexistence of multiple clonal cytogenetic abnormalities, referred to as complex karyotype (CK), has been associated with the worst outcome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with good risk cytogenetics such as abn [16] or t(8; 21) can be spared from the toxicity of SCT, while patients with high risk cytogenetics appear to benefit from SCT, with an estimated 44% probability of surviving 5 years after CR1, compared with 15% or less after chemotherapy [2]. Several reports have confirmed this significant advantage of SCT in high risk AML, and it is currently highly recommended not to delay SCT in this population [3][4][5]. Among patients with high risk AML, the coexistence of multiple clonal cytogenetic abnormalities, referred to as complex karyotype (CK), has been associated with the worst outcome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of cooperative groups have incorporated unrelated donor alloHSCT in their protocols for upfront treatment of AML patients, as multiple retrospective and prospective studies have shown that -well matched‖ unrelated donor grafts may be associated with acceptable NRM and strong reduction of relapse in AML CR1 patients (69-76). In the recent prospective study of the German Austrian AML Study Group, equivalent efficacy and NRM was shown in a head to head comparison of matched related and unrelated donor alloHSCT in adult high-risk patients (76). Collectively, these studies suggest that an unrelated donor alloHSCT is justified if the a priori risk of relapse is sufficiently high and the counterbalancing NRM following unrelated donor alloHSCT can be estimated as moderate.…”
Section: Predicting Counterbalancing Non Relapse Mortality (Nrm)mentioning
confidence: 93%
“…(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). During the prospective German-Austrian study (76), a growing number of patients received RIC-regimens. Although not randomized, that study prospectively suggested equivalent results in patients receiving RIC or MA regimen in terms of relapse, NRM, and survival.…”
Section: Predicting Counterbalancing Non Relapse Mortality (Nrm)mentioning
confidence: 99%
“…Recently, several groups have conducted prospective donor vs no-donor studies for AML patients with high-risk features by expanding the type of donor to include unrelated donors. [19][20][21] Notably, despite a limited number of patients in each study, they showed significantly superior OS in patients with a donor, as well as comparable OS in patients undergoing related and unrelated HCT. [19][20][21] These prospective studies also support the usefulness of unrelated HCT in younger AML patients with non-favorable cytogenetics.…”
Section: Discussionmentioning
confidence: 89%
“…[19][20][21] Notably, despite a limited number of patients in each study, they showed significantly superior OS in patients with a donor, as well as comparable OS in patients undergoing related and unrelated HCT. [19][20][21] These prospective studies also support the usefulness of unrelated HCT in younger AML patients with non-favorable cytogenetics. Although our multivariate analysis showed that the degree to which allogeneic HCT had favorably affected outcome was less marked in patients without a related donor compared with those with a related donor, unrelated HCT could be considered a reasonable treatment option if a related donor is not available.…”
Section: Discussionmentioning
confidence: 89%